Assessing the impact of ecosystem factors on oil palm smallholder productivity: Evidence from Bakong and Marudi, Sarawak - Idris, Muhammad Yusuf; Tahir, Zurinah; Ishak, Suraiya; Azian, Fatin Umaira Muhamad; Lyndon, Novel (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to assess the impact of six components of a conducive ecosystem on the productivity of oil palm smallholders in Bakong and Marudi, Sarawak. The components examined include safety, family labour, effective leadership, technology, environmental conditions, and collaborative networks. Despite extensive research on agricultural productivity, limited empirical studies have systematically evaluated how these interrelated ecosystem factors affect smallholder performance, particularly within the context of the Malaysian palm oil industry. Addressing this gap, the study offers a contextualised analysis of ecosystem-based productivity determinants in a key producing region. A quantitative approach was employed using a cross-sectional survey design involving 345 randomly selected smallholders from the Malaysian Palm Oil Board (MPOB) Miri Branch database. Data were collected through a structured questionnaire and analysed using descriptive statistics and multiple regression analysis. The findings reveal that all six ecosystem components positively influence smallholder productivity, with safety demonstrating the strongest impact (30.55%). However, only three components safety, family labour, and effective leadership were identified as statistically significant predictors. These results support the economic production theory and Maslow’s hierarchy of needs, highlighting the importance of both physical inputs and motivational factors in achieving optimal agricultural output. The study contributes novel insights by integrating both tangible and intangible ecosystem components within a unified analytical framework. It proposes that smallholder development strategies adopt an ecosystem-based approach, emphasizing farm security, community empowerment, and appropriate technology adoption. The findings have important implications for policy formulation and the advancement of sustainable practices in the palm oil industry.